1997
DOI: 10.1016/s0001-4575(97)00012-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of administrative license revocation on employment

Abstract: PREFACEThis research project evaluated both the effects of administrative license revocation (ALR) on the employment of first and multiple DUI offenders and the effects of alcohol-involved crashes on the employment of the victims of these crashes.The authors would like to recognize the following organizations The authors would also like to thank Mr. Steven Schmidt, formerly of the PA DUI Association, for his assistance throughout the project and the following KETRON team members who assisted with site selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…There have been some qualitative interview studies with unlicensed drivers (e.g. Clark & Bobevski, 2008;Ferrante, 2003;Knox et al, 2003;Mirrlees-Black, 1993;Ross & Gonzales, 1988;Silcock, Sunter, van Lottum, & Beuret, 1999), some quantitative mail questionnaire studies (Chang, Woo, & Tseng, 2006;Robinson & Kelso, 1981;Smith & Maisey, 1992;Williams et al, 1984), a quantitative interview study (Wells-Parker & Cosby, 1988) and classroom completed questionnaire study (Knoebel & Ross, 1997). It has been noted that much of the research on unlicensed driving is purely descriptive and fails to illuminate the personal, social and environmental factors underpinning the behaviour and consequently why, employment, family or social factors lead some to drive without a valid licence (Watson, 2003).…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some qualitative interview studies with unlicensed drivers (e.g. Clark & Bobevski, 2008;Ferrante, 2003;Knox et al, 2003;Mirrlees-Black, 1993;Ross & Gonzales, 1988;Silcock, Sunter, van Lottum, & Beuret, 1999), some quantitative mail questionnaire studies (Chang, Woo, & Tseng, 2006;Robinson & Kelso, 1981;Smith & Maisey, 1992;Williams et al, 1984), a quantitative interview study (Wells-Parker & Cosby, 1988) and classroom completed questionnaire study (Knoebel & Ross, 1997). It has been noted that much of the research on unlicensed driving is purely descriptive and fails to illuminate the personal, social and environmental factors underpinning the behaviour and consequently why, employment, family or social factors lead some to drive without a valid licence (Watson, 2003).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…A number of previous studies found that only a small proportion of drivers who lose their licence due to driving under the influence of alcohol had resultant employment and income problems, primarily because many drivers continued to drive while suspended (e.g. Knoebel & Ross, 1997;Ross & Gonzales, 1988;Wells-Parker & Cosby, 1988). In another Western Australian study Ferrante (2003) found the greatest impact of licence disqualification was on employment and family responsibilities.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Finally, the privilege to drive is highly valued, and withdrawal of the privilege feared (DeYoung and Gebers, 2004). Even for a short-term S/R, one-fifth of the US states rejected the adoption of administrative S/R because it could lead to loss of employment, in turn impacting the offender's dependents and subsequent social welfare costs (Knoebel and Ross, 1997;Voas and DeYoung, 2002). In 2001, the transportation authority has been requested by the Taiwan Constitutional Court to seriously reconsider whether ALLR offenders should be allowed to re-enter the licensing system if they can demonstrate their ability and willingness to follow the regulations of the road and society.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, offenders might be unable to commute to work as a result of license sanctions. However, evidence has suggested that 94% of offenders continue to work 1 month after their license suspensions ( Knoebel & Ross, 1997 ). It is important to note that some of these states polled do allow for limited licenses.…”
Section: Targeted and Selected Interventionsmentioning
confidence: 99%